1996
DOI: 10.1074/jbc.271.17.10217
|View full text |Cite
|
Sign up to set email alerts
|

Ras, Rap, and Rac Small GTP-binding Proteins Are Targets for Clostridium sordellii Lethal Toxin Glucosylation

Abstract: Lethal toxin (LT) fromClostridium sordellii is one of the high molecular mass clostridial cytotoxins. On cultured cells, it causes a rounding of cell bodies and a disruption of actin stress fibers. We demonstrate that LT is a glucosyltransferase that uses UDP-Glc as a cofactor to covalently modify 21-kDa proteins both in vitro and in vivo. LT glucosylates Ras, Rap, and Rac. In Ras, threonine at position 35 was identified as the target amino acid glucosylated by LT. Other related members of the Ras GTPase super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(166 citation statements)
references
References 30 publications
3
160
0
3
Order By: Relevance
“…The biological function of Rap1 is still unclear, but it has been proposed that activation of this small GTPase may feed into MAPK signaling pathways (50). As an approach to establishing if Rap1 has a role in cyclic AMPmediated delay of neutrophil apoptosis, we have blocked Rap1 activity using the Clostridium sordellii lethal toxin, which has been reported to inhibit specifically the small GTPases Rap1, Ras, and Rac (51). Furthermore, we have tested GGTI-286, a geranylgeranyltransferase inhibitor, which blocks geranylgeranylation required by Rap1 to achieve its mature, biologically active form (52).…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of Rap1 is still unclear, but it has been proposed that activation of this small GTPase may feed into MAPK signaling pathways (50). As an approach to establishing if Rap1 has a role in cyclic AMPmediated delay of neutrophil apoptosis, we have blocked Rap1 activity using the Clostridium sordellii lethal toxin, which has been reported to inhibit specifically the small GTPases Rap1, Ras, and Rac (51). Furthermore, we have tested GGTI-286, a geranylgeranyltransferase inhibitor, which blocks geranylgeranylation required by Rap1 to achieve its mature, biologically active form (52).…”
Section: Discussionmentioning
confidence: 99%
“…Of the kinases shown, only MKK7 and JNK1 have been shown to be activated in vivo [42,43]. which glucosylates and thereby inactivates Ras, Rac, and Rap [51]. We have found that LT inhibits p38 and p42/p44 MAP kinase activation by IL-1 in EL4 cells [52].…”
Section: Is a Low-molecular-weight G Protein Involved In Il-1 Signaling?mentioning
confidence: 99%
“…The family of large clostridial cytotoxins inactivate small GTPases by glucosylation (28). Whereas Clostridium difficile toxins A and B monoglucosylate Rho GTPases including Rho, Rac, and Cdc42 at Thr-37 or Thr-35, respectively (29), the lethal toxin from Clostridium sordellii modifies Rac, possibly Cdc42, but not Rho (30,31). In addition, Ras subfamily proteins (e.g.…”
Section: Cross-linking Of the High Affinity Ige Receptor (Fc⑀ri)mentioning
confidence: 99%